Climate resilient livestock-based agro-forestry systems in north east india: productivity, carbon dynamics and livelihood implications - Murali Arthanari Palanisamy; Rajib Das; Joy Kumar Dey; Kiruthika Rajamanickam; Mahamaya Banik; Ajit Kumar Mandal; Jitendra Kumar; Shatabhisa Sarkar; Mainak Ghosh; Prasanta Kumar Pathak; A. K. Mohanty (Agroforestry Systems, 2026)

Green Synthesized Cu-Co Doped ZnO/D-Carvone Modified Biochar for Dual Photocatalytic-Adsorptive Elimination of Methylene Blue under UV Irradiation - Eksha Guliani; Vinayak V. Pathak; Sangita Banga; Sudhish K. Shukla; Shailendra K. Singh; Amit Awasthi; Sumanta Das; Malini Roy Choudhury (Water, Air, & Soil Pollution, 2026)

Galectin-3, transforming growth factor beta 1, and brain natriuretic peptide in cardiac remodeling under hyperlipidemic and hyperglycemic stress - Hina Patel; Angelie Pathak; Resmi Rajalekshmi; Brian David; Devendra K. Agrawal (Molecular and Cellular Biochemistry, 2026)
Hyperlipidemia (HYL) and hyperglycemia (HYG) directly drive pathological cardiac remodeling; however, the mechanisms by which these conditions differentially regulate profibrotic signaling and early stress‑response pathways in left ventricular (LV) myocardium remain poorly defined. This study investigated the expression and localization of galectin-3 (Gal-3), transforming growth factor-β1 (TGF-β1), and brain natriuretic peptide (BNP) in a Yucatan miniswine model of HYL and HYG. Female Yucatan miniswine were assigned to normal control, HYL (high-cholesterol diet), or HYG (high-fat/high-carbohydrate diet plus low dose streptozotocin) groups ( n = 6/group) for 8-weeks, and LV tissue was assessed by histology, qRT-PCR, Western blot, and immunohistochemistry. Both metabolic conditions induced cardiomyocyte hypertrophy and interstitial fibrosis, with more diffuse collagen deposition in HYG myocardium. qRT-PCR demonstrated upregulation of Gal-3, TGF-β1, and BNP relative to controls, with transcript levels positively correlating with circulating glucose concentration. Western blot analysis showed relatively greater active TGF-β1 signal in HYL myocardium and greater latent precursor accumulation in HYG myocardium, suggesting condition-associated differences in TGF-β1 regulation. Immunohistochemistry demonstrated perivascular Gal-3 localization, cytoplasmic and perinuclear TGF-β1 immunoreactivity in cardiomyocytes, and BNP immunoreactivity predominantly within subendocardial Purkinje fibers, with increased staining intensity in metabolically stressed groups compared with controls. Collectively, these findings suggest that HYL and HYG are associated with overlapping but distinct patterns of Gal-3, TGF-β1, and BNP expression during metabolic cardiac remodeling. The Gal-3/TGF-β1 axis may represent a shared profibrotic pathway, whereas BNP may reflect a compensatory stress response whose functional significance requires further mechanistic validation.

Integrated pond co-culture of Penaeus vannamei with red seaweeds: Implications for nutrient uptake and dual production performance - K. Surya; Madhuri Pathak; Munilkumar Sukham; Thongam Ibemcha Chanu; Layana Porayil; Vaibhav A. Mantri; Debajit Sarma; G. Harini; P.S. Prathib; Bhavik Kantilal Bhagiya; Komal R. Chilveri (Algal Research, 2026)

Effect of nanoparticles on morpho-histology of Eri silkworm, Samia cynthia ricini (Boisduval) (Lepidoptera: Saturniidae) - Hia Kalita; Mahesh Pathak; Sudharshan KR; Bimal Kumar Sahoo; Sikha Haritha; Pranab Dutta; Kennedy Ningthoujam; Raghubir K. Patidar (International Journal of Tropical Insect Science, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Strengthening the teleconnection pathway: Improving ISMR predictability through the West North Pacific in the coupled model - Vishal N. Pathak; Renu S. Das; Deepesh K. Jain; Ashish Alone (Dynamics of Atmospheres and Oceans, 2026)

Water Use in Rice Crop Cultivation in India: A Quantitative Assessment - Manish Debnath; Sumanta Chatterjee; A. K. Nayak; D. Chakraborty; H. Pathak (Agricultural Research, 2026)

Imperatorin, a natural furanocoumarin alleviates chronic neuropathic pain by targeting GABAergic tone in an animal model of spinal cord injury - Ayub Mohammed Butt; Manjeet Chopra; Ankita Bhagwani; Zarna Pathak; Kishori Jadhav; Rohini Jadhav; Pooja Tarde; Parusu Kavya Teja; Suraj Kutre; A. Hariharan; Alisha Vartak; Siddheshwar K. Chauthe; et al. (Natural Product Research, 2026)

Synthesis and bioactivity assessment of trisindoline derivatives as agrochemical agents - Gurbir Kaur; Divya Utreja; Anu Kalia; Sukhjeet Kaur; Rajesh K. Pathak; Harwinder Singh Buttar (European Journal of Plant Pathology, 2026)

Environmental risks associated with PFAS contamination in water: Challenges and emerging management strategies - Monika Mahajan; Rajneesh Kumar Gautam; Himanshu K. Pathak; Rajeev Pratap Singh; Edza Aria Wikurendra (Current Opinion in Environmental Science & Health, 2026)

Elucidating the Conjoint Effect of Nano, Conventional and Bio-Fertilizer on Steering Sugarcane Productivity, Quality and Soil Health - Mona Nagargade; Vishal Tyagi; Dileep Kumar; Sudhir Kumar Shukla; Preeti Singh; Rajeev Kumar; Ashwini Dutt Pathak; V. P. Jaiswal; M. K. Tripathi; A. P. Dwivedi; Lalan Sharma; Sanjay Singh Rathore; et al. (International Journal of Plant Production, 2026)

Revealing the Growth, Osmoregulation, Biochemical Composition and Histological Alterations in Pacific White Shrimp Penaeus vannamei Reared in Potassium Fortified Inland Saline Groundwater - Madhuri S. Pathak; Appidi K. Reddy; G. Venkateshwarlu; Wazir S. Lakra (Agricultural Research, 2026)

Potential Impact of Heavy Metals and Microplastics in River Ecosystem on Aquatic Organisms and Human Health, and Sustainable Mitigation Approaches - Himanshu K. Pathak; Kavita Gandhi; Rajeev Pratap Singh (Water, Air, & Soil Pollution, 2026)

Biotechnological valorization of waste oyster shell as an antifungal agent: Chemical analysis, molecular docking, and ADMET insights - Smarajit Adhya; Sampuran Saha; Suryadeep Kanji; Sudipta K Das; Sharbadeb Kundu; Baisnabdas Pathak; Sekhar Pal; Sandhimita Mondal (Next Research, 2025)

Impact of hidden hunger on pregnant women from underserved communities and its role in anaemia - Anumesh K. Pathak; Dhruv Agarwal; Shivani Singh; Rupita Kulshresthra; Manish Raj Kulshrestha; Vandana Tiwari (Journal of Trace Elements in Medicine and Biology, 2025)

NPF-induced CCN enhancement over an urban location in Eastern Himalayan Foothills: A campaign-based study - Barlin Das; Binita Pathak; Uday Bhattacharjee; Partha Jyoti Sahu; Arundhati Kundu; Arup Borgohain; Mukunda M. Gogoi; Shyam S. Kundu; Kalyan Bhuyan; Pradip K. Bhuyan (Atmospheric Environment, 2025)

Klotho protein: a multifaceted regulator in aging and cancer dynamics - Sibin Nambidi; Sneha Pallatt; Antara Banerjee; Surajit Pathak; Mike K. S. Chan (Molecular Biology Reports, 2025)

A pilot study on the efficacy of a telomerase activator in regulating the proliferation of A375 skin cancer cell line - M. K. Makalakshmi; Antara Banerjee; Surajit Pathak; Sujay Paul; Neeta Raj Sharma; B. Anandan (Molecular Biology Reports, 2025)

Targeting west nile virus replication by xanthine inhibitors - Theresa H. Nguyen; Jessica L. Smith; Shuklendu D. Karyakarte; John P. Tillotson; Sarath C. Sarngadharan; Fuad Al Abir; Jake Y. Chen; Sixue Zhang; Lynn Rasmussen; Robert Bostwick; Alec J. Hirsch; Corinne E. Augelli-Szafran; et al. (Medicinal Chemistry Research, 2025)

Metabolic engineering of lipids for crop resilience and nutritional improvements towards sustainable agriculture - Swati Mangla; Yogesh K. Ahlawat; Gaurav Pathak; Nisha Sharma; Maryam Samani; Veer Bhan; Jemaa Essemine; Yashirdisai Sampasivam; Navjot Singh Brar; Anurag Malik; Vikas Ramteke; Shivali Gupta; et al. (Functional & Integrative Genomics, 2025)

Climate Resilient Crop Varieties: Mainstreaming to Improve Yield and Moderate Farmers’ Risk - D. K. Yadava; Ranjay K. Singh; V. B. Patel; T. R. Sharma; S. K. Singh; Sudhakar Pandey; P. R. Choudhury; Firoz Hossain; R. R. Burman; U. S. Gautam; Himanshu Pathak (Anthropocene Science, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Steroidal glycoside-rich extract of fenugreek seeds mitigates obesity-induced insulin resistance via attenuation of low-grade inflammation - Sumati Sen; Ashutosh K. Tiwari; Monika Binwal; Monazza Israr; Anant Kumar; Nandini Pathak; Kaveri R. Washimkar; CH Ratnasekhar; Madhav Nilakanth Mugale; Arvind S. Negi; Dnyaneshwar U. Bawankule (Food Research International, 2025)

Fruit tree-based restoration strategy to mitigate greenhouse gas emissions, and enhance the profitability of degraded land in semi-arid tropics - R. Siddesh; Himanshu Pathak; S.B. Chavan; Hanamant M. Halli; V.D. Kakade; A.S. Morade; Sanjni Salunkhe; D.D. Nangare; V.N. Salunkhe; A.K. Singh; Aliza Pradhan; K. Sammi Reddy (Science of The Total Environment, 2025)

Detection of elevated CO₂ and CH₄ emissions from power plant and landfill sites using airborne and spaceborne imaging spectroscopy - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Dhruv D. Desai; Manoj Singh; Dhiraj B. Shah; Vishal N. Pathak; Himanshu J. Trivedi (Atmospheric Pollution Research, 2025)

Recent advancement on nanotechnology and natural compounds for skin UV protection: a review - M. J. Saadh; V. Jain; M. M. Rekha; P. K. Pathak; H. M. Ahmed; K. Satyam Naidu; B. Juneja; F. Faez Sead; M. Dehghanipour (International Journal of Environmental Science and Technology, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Colorectal Cancer Mitigation Through Probiotics: Current Evidence and Future Directions - Priyanka Chaturvedi; Rimjhim Pathak; Ranu Dayal; Himani Parihar; Alagapuram K. Kathireshan; Prem S. Tirumalai (Current Microbiology, 2025)

Synergistic Effects of Pollarding and Chlormequat Chloride on Growth, Yield, Quality, and Pest-Disease Incidence in Papaya cv. F1-Red Lady Under Controlled Cultivation - Suvrajit Patra; Sonu Nagar; K. M. Renuka Swamy; Anshuman Pathak; Neeharika Kanth; Sanjay Kumar Singh; Gangadhar Nanda; Asish Kumar Panda (Journal of Plant Growth Regulation, 2025)

Mapping of deep pool habitats in the rivers of water deficit Bundelkhand region: a novel approach for fish conservation and sustainable management - Ganesan Kantharajan; Shubham Kanaujiya; Uttam Kumar Sarkar; Rejani Chandran; Ajey Kumar Pathak; Tarachand Kumawat; Rajeev K. Singh (Environmental Monitoring and Assessment, 2025)

Microalgae as a sustainable source of carotenoids: Strategies to improve yield and productivity - Wan Adibah Wan Mahari; Wan Aizuddin Wan Razali; Yoong Kit Leong; Vishal Sharma; Vaibhav Sunil Tambat; Himanshu K. Pathak; Nyuk Ling Ma; Siew-Moi Phang; Cheng-Di Dong; Su Shiung Lam (Journal of Environmental Chemical Engineering, 2025)

Appraisal on Energy Coefficients in Energetic Analysis of Agricultural Production System and Energetic Assessment on Sugarcane production - P. Subramanian; R. Mahendiran; B. Prabha; Gitanjali Jothiprakash; Ramesh Desikan; Bhargav Vinod Kumar; K. C. Pandey; Bhim Sen Pathak (Sugar Tech, 2025)

Integration of Bioproducts with NPK for Improving Physiological Efficiency of Sugarcane and Sustaining Soil Quality Parameters in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak; Asha Gaur; Abhay Srivastava; Rishi Kumar; Mamta Chaoudhary (Sugar Tech, 2025)

Habitat suitability mapping of chocolate mahseer, Neolissochilus hexagonolepis (McClelland, 1839) in the Teesta River basin, Indian Himalayan region for conservation - Vijay Kumar; Ganesan Kantharajan; Lalit Kumar Tyagi; Achal Singh; Rejani Chandran; A. K. Pathak; Amit Singh Bisht; L. Mog Chowdhury; Rajeev K. Singh; Uttam Kumar Sarkar (Spatial Information Research, 2025)

Combined Genome-Wide Association Study and Expression Analysis Unravels Candidate Genes Associated with Seed Weight in Moth Bean [Vigna aconitifolia (Jacq.) Marechal] - Arvind Kumar Yadav; Chandan Kumar Singh; Dhammaprakash P. Wankhede; Rajwant K. Kalia; Seema Pradhan; Shraddha Ujjainwal; Tanmaya Kumar Sahu; N. S. Nathawat; R. K. Kakani; Reena Rani; Rajesh Kumar; Rakesh Pathak; et al. (Journal of Plant Growth Regulation, 2025)

Integration of Mycorrhizae, Azotobacter and Pseudomonas spp (PSB) with NPK and their Effects on Sugarcane Crop and Soil Health in Uttar Pradesh, India - M. K. Tripathi; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Mona Nagargade; A. D. Pathak; A. P. Dwivedi; Ankur Tripathi; V. K. Singh; V. P. Singh; Ajay Ranka (Sugar Tech, 2025)

Space based thermal and airborne hyperspectral data in REE exploration − A study in Siwana ring complex, Rajasthan, India - Arindam Guha; Suparn Pathak; Sushil K. Srivastav; Ritesh Purohit; M. Kar; Prakash Chauhan (Advances in Space Research, 2025)

Association of Arsenic and Nickel with Markers of Insulin Resistance and Beta Cell Dysfunction: A Case–Control Study in Indo Gangetic Plain - Shefali Singh; Juhi Verma; Nikhil Gupta; Anumesh K. Pathak; Manish Singh Rajput; Vandana Tiwari; Manish Raj Kulshrestha (Biological Trace Element Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Flow-by-Flow Paleofield and Virtual Dipole Moment Analysis in the Mandla Lobe, Eastern Deccan Volcanic Province - Bhuvan K. Tamta; Vamdev Pathak; J. P. Shrivastava; Arun Kumar Gupta; Girish Ch. Kothyari (Pure and Applied Geophysics, 2025)

Energy, exergy, and economic analysis of solar still integrated with phase change material assimilated evacuated tube collector for wastewater treatment - Atin Kumar Pathak; V.V. Tyagi; K. Chopra; Mriduta Sharma; Sanjeev Anand; Richa Kothari; A.K. Pandey (Process Safety and Environmental Protection, 2025)

A hybrid physics-based method for estimating land surface temperature using radiative transfer simulations and machine learning model from Sentinel-3A SLSTR observations - Jalpesh A. Dave; Vedant Pandya; Frank-M. Goettsche; Hasmukh K. Varchand; Parthkumar N. Parmar; Dhruv D. Desai; Disha B. Kardani; Dhiraj B. Shah; Ashwin Gujrati; Vishal N. Pathak; Himanshu J. Trivedi; Mehul R. Pandya (Earth Science Informatics, 2025)

Genomic Insights of Multidrug-Resistant Enterococcus faecalis and Acinetobacter baumannii Isolated from a Sepsis Patient with Pauci-Immune Crescentic Glomerulonephritis, India - Ujjayni B. Saha; Kunal K. Dixit; Savita V. Jadhav; Ketaki N. Pathak; Neetu S. Gupta; Sunil D. Saroj (Current Microbiology, 2025)

Unlocking synergies: Enhancing bioremediation, growth, and physiological responses of Penaeus vannamei co-cultured with seaweed - G. Harini; Madhuri S. Pathak; Sukham Munilkumar; Kapil S. Sukhdhane; Thongam Ibemcha Chanu; Amjad K. Balange; K. Jeena (Algal Research, 2025)

Effect of Tween 80 and Pluronic 127 on the stabilization of zein nanocarriers for the delivery of piperine - K Sivasankar; Anchal Pathak; Keerti Jain (Food Research International, 2024)

Zinc Adsorption–Desorption Behavior and Sequential Extractable Pools in Sugarcane-Based Cropping Systems of Western Indo-Gangetic Plain - Shivam Singh; Satendra Kumar; Debashis Dutta; Richa Raghuvanshi; Jagannath Pathak; Uday Pratap Shahi; B. P. Dhyani; Ankit Kumar; Mahendra Pratap Singh; Himanshu Panday; A. K. Shah (Sugar Tech, 2024)

Efficiency and economic assessment of wind turbine-powered pumped hydro-compressed air storage coupled with alkaline fuel cell using hybrid approach - K. E. Lakshmiprabha; U. Arun Kumar; Pankaj Pathak; P. Elangovan (Clean Technologies and Environmental Policy, 2024)

Crustal origin for olivine in the lunar Shioli crater ejecta boulders: Insights from the geological setting of Theophilus crater and Nectaris basin - P. Senthil Kumar; Abhisek Mishra; Vivek Krishnan; Netra S. Pillai; Sumit Pathak; Sriram S. Bhiravarasu; Shyama Narendranath; K. Jaya Prasanna Lakshmi; Satadru Bhattacharya (Icarus, 2024)

A brief overview of SARS-CoV-2 infection and its management strategies: a recent update - Alakesh Das; Surajit Pathak; Madhavi Premkumar; Chitra Veena Sarpparajan; Esther Raichel Balaji; Asim K. Duttaroy; Antara Banerjee (Molecular and Cellular Biochemistry, 2024)
The COVID-19 pandemic has become a global health crisis, inflicting substantial morbidity and mortality worldwide. A diverse range of symptoms, including fever, cough, dyspnea, and fatigue, characterizes COVID-19. A cytokine surge can exacerbate the disease’s severity. This phenomenon involves an increased immune response, marked by the excessive release of inflammatory cytokines like IL-6, IL-8, TNF-α, and IFNγ, leading to tissue damage and organ dysfunction. Efforts to reduce the cytokine surge and its associated complications have garnered significant attention. Standardized management protocols have incorporated treatment strategies, with corticosteroids, chloroquine, and intravenous immunoglobulin taking the forefront. The recent therapeutic intervention has also assisted in novel strategies like repurposing existing medications and the utilization of in vitro drug screening methods to choose effective molecules against viral infections. Beyond acute management, the significance of comprehensive post-COVID-19 management strategies, like remedial measures including nutritional guidance, multidisciplinary care, and follow-up, has become increasingly evident. As the understanding of COVID-19 pathogenesis deepens, it is becoming increasingly evident that a tailored approach to therapy is imperative. This review focuses on effective treatment measures aimed at mitigating COVID-19 severity and highlights the significance of comprehensive COVID-19 management strategies that show promise in the battle against COVID-19.

Recent advancement of nano-biochar for the remediation of heavy metals and emerging contaminants: Mechanism, adsorption kinetic model, plant growth and development - Himanshu K. Pathak; Chandra Shekhar Seth; Prabhat K. Chauhan; Gopal Dubey; Garima Singh; Devendra Jain; Sudhir K. Upadhyay; Padmanabh Dwivedi; Kuan Shiong Khoo (Environmental Research, 2024)

Transfluthrin is Associated with High Susceptibility to Asthma in Children with Promoter Variants of Beta Chain of High-Affinity Receptor IgE and Tumour Necrosis Factors-α Genes - Shivani Singh; Manish Raj Kulshrestha; Anumesh K. Pathak; Shetanshu Srivastava; Aditi Singh; Vandana Tiwari (Biochemical Genetics, 2024)

Alzheimer’s disease: from early pathogenesis to novel therapeutic approaches - Santosh Kumar Prajapati; Arjit Pathak; Puneet K. Samaiya (Metabolic Brain Disease, 2024)

Mechanistic and future prospects in rhizospheric engineering for agricultural contaminants removal, soil health restoration, and management of climate change stress - Himanshu K. Pathak; Prabhat K. Chauhan; Chandra Shekhar Seth; Gopal Dubey; Sudhir K. Upadhyay (Science of The Total Environment, 2024)

Prevalence and risk factor for H9N2 avian influenza virus in poultry retail shops of Madhya Pradesh - Baleshwari Dixit; H. V. Murugkar; S. Nagarajan; C. Tosh; Manoj Kumar; Anubha Pathak; Sivasankar Panickan; Neeraj Shrivastav; Anjani K. Mishra; Manu Dixit (VirusDisease, 2024)

Impact of Bacillus cereus SPB-10 on Growth Promotion of Wheat (Triticum aestivum L.) Under Arsenic-Contaminated Soil - Prabhat K. Chauhan; Himanshu K. Pathak; Gopal Dubey; Hritik Sharma; Sudhir K. Upadhyay (Current Microbiology, 2024)

Integration of apocarotenoid and transcriptome profiles of developing stigmas of saffron (Crocus sativus L.) reveals a multifaceted control involving PSY2, OR-a, PIF1 and HY5 genes in regulation of apocarotenoid biosynthesis - Mona H. Thakuri; Upasna Chettry; Jyoti Pathak; Nikhil K. Chrungoo (South African Journal of Botany, 2024)

Fatty Acids and their Proteins in Adipose Tissue Inflammation - Rahul Mallick; Sanjay Basak; Ranjit K. Das; Antara Banerjee; Sujay Paul; Surajit Pathak; Asim K. Duttaroy (Cell Biochemistry and Biophysics, 2024)
Chronic low-grade adipose tissue inflammation is associated with metabolic disorders. Inflammation results from the intertwined cross-talks of pro-inflammatory and anti-inflammatory pathways in the immune response of adipose tissue. In addition, adipose FABP4 levels and lipid droplet proteins are involved in systemic and tissue inflammation. Dysregulated adipocytes help infiltrate immune cells derived from bone marrow responsible for producing cytokines and chemokines. When adipose tissue expands in excess, adipocyte exhibits increased secretion of adipokines and is implicated in metabolic disturbances due to the release of free fatty acids. This review presents an emerging concept in adipose tissue fat metabolism, fatty acid handling and binding proteins, and lipid droplet proteins and their involvement in inflammatory disorders.

To Detect Aerosols Optical Depth (AOD) Local Hotspot Region: Spatiotemporal Characteristics over Indian Regions - Ranjitkumar Solanki; K. N. Pathak (Aerosol Science and Engineering, 2024)

Adoption of Trench Method Cane Planting and its Role in Increasing Cane Yield and Sugar Recovery in Uttar Pradesh - S. K. Pathak; R. A. Kushwaha; A. K. Sah (Sugar Tech, 2024)

CO2 concentration retrieval and emission rate estimation over Indian thermal power plants using radiative transfer approach and AVIRIS-NG data - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Himanshu J. Trivedi; Dhiraj B. Shah; Vishal N. Pathak (Remote Sensing Applications: Society and Environment, 2024)

Distribution and concentration pathway of particulate pollution during pandemic-induced lockdown in metropolitan cities in India - A. Anand; V. K. Garg; A. Agrawal; S. Mangla; A. Pathak (International Journal of Environmental Science and Technology, 2024)

Detection and mapping of vegetation stress using AVIRIS-NG hyperspectral imagery in coal mining sites - Narayan Kayet; Khanindra Pathak; C.P. Singh; Bimal K. Bhattacharya; Rajiv Kumar Chaturvedi; AnjaniKumar SV Brahmandam; Chinmoy Mandal (Advances in Space Research, 2024)

Comparative evaluation of native top feeds of western Himalayas for utilization as goat’s ration in mash and block form - Imran Ahmad Ganai; R. K. Sharma; Ankur Rastogi; A. K. Pathak; Vijay Kumar Sharma (Tropical Animal Health and Production, 2023)

Space based Earth observation approach for exploring hydrocarbon prospects in an intracratonic rift basin – A study in north Cambay basin, Gujarat - Arindam Guha; Nikhil Kumar Baranval; Ashish Misra; Swati Singh; M. Shivashankar; Santosh Garain; Subhobroto Mazumder; S. Pathak; K. Vinod Kumar (Advances in Space Research, 2023)

A search for potential anti-HIV phytoconstituents from the natural product repository - Dharmraj V. Pathak; Sneha R. Sagar; Hardik G. Bhatt; Paresh K. Patel (Advances in Traditional Medicine, 2023)

BMAP-27 Peptide Reduces Proliferation and Increases Apoptosis in Primary and Metastatic Colon Cancer Cell Lines - Alakesh Das; Dikshita Deka; Nabajyoti Baildya; Antara Banerjee; Atil Bisgin; Suman Adhikari; Asim K. Duttaroy; Surajit Pathak (International Journal of Peptide Research and Therapeutics, 2023)
BMAP-27 peptide is reported to possess apoptotic and anti-proliferative effects against cancer cells but the actual mechanism of action is yet to be investigated. In the current investigation, we aimed to study the role of the BMAP-27 peptide in reducing proliferation and increasing apoptosis in colon cancer cell lines. In this study, we used primary and metastatic colon cancer cell lines SW480 and SW620. Cell proliferation was measured using MTT and CCK-8 assays, and cellular damage was analyzed by lactate dehydrogenase assay. Apoptosis, cell cycle, and proliferation potentials were measured by the expression of CASPASE3, BAX, BCL-2, TP53, CDK-6, PCNA, WNT11, AXIN1 , and CTNNB1 genes. Additionally, in-silico studies were conducted to determine the binding affinities of BMAP-27 with adenomatous polyposis coli (APC) and β-catenin proteins, one of the primary regulators of colon cancer. BMAP-27 peptide reduced colon cancer cell proliferation, upregulated tumor suppressor genes CASPASE3, BAX, TP53, AXIN1 expression, and downregulated the expression of oncogenes BCL-2, CDK-6, PCNA, WNT11, CTNNB1 in both the cell lines, however, in the primary colon cancer cell line the changes are found to be more significant. The molecular dynamic simulation analysis revealed substantial binding affinity of the peptide to APC and β-catenin proteins. BMAP-27 peptide significantly inhibited the proliferation and induced apoptosis in the primary colon cancer cell line than in the metastatic colon cancer cell line. In-silico results suggest that BMAP-27 shows a strong binding affinity with APC and β-catenin proteins, highlighting its role in inhibiting colon cancer cell proliferation.

Exosomes from metastatic colon cancer cells drive the proliferation and migration of primary colon cancer through increased expression of cancer stem cell markers CD133 and DCLK1 - K. Yasodha; L. Lizha Mary; Pathak Surajit; R. Satish (Tissue and Cell, 2023)

The impact of different fertiliser management options and cultivars on nitrogen use efficiency and yield for rice cropping in the Indo-Gangetic Plain: Two seasons of methane, nitrous oxide and ammonia emissions - Arti Bhatia; Nicholas J. Cowan; Julia Drewer; Ritu Tomer; Vinod Kumar; Shikha Sharma; Ankita Paul; Niveta Jain; Sandeep Kumar; Girish Jha; Renu Singh; Radha Prasanna; et al. (Agriculture, Ecosystems & Environment, 2023)

Indian summer monsoon simulations in successive generations of the NCAR Community Atmosphere Model - Ravi Kumar; Raju Pathak; Sandeep Sahany; Saroj K. Mishra (Theoretical and Applied Climatology, 2023)

Potential avenue of genetic engineered algal derived bioactive compounds: influencing parameters, challenges and future prospects - Richa Kothari; Har Mohan Singh; Rifat Azam; Kajol Goria; Anu Bharti; Anita Singh; Somvir Bajar; Ashish Pathak; A. K. Pandey; V. V. Tyagi (Phytochemistry Reviews, 2023)

Scoping the Need of Mainstreaming Indigenous Knowledge for Sustainable Use of Bioresources in the Indian Himalayan Region - Vikram S. Negi; Ravi Pathak; Shinny Thakur; Ravindra K. Joshi; Indra D. Bhatt; Ranbeer S. Rawal (Environmental Management, 2023)

Enhancing Crop Productivity and Profitability of Autumn Sugarcane with Intercropping of Winter Vegetables in Real Farming Situations of North-Central India - S. N. Singh; Chandra Gupta; V. K. Singh; A. D. Pathak; A. K. Sah; M. K. Tripathi; Sanjiv Gupta; J. R. Patnaik (Sugar Tech, 2023)

Observations on the decadal variability of aerosol in eastern Himalayan foothills: Evidence of an anthropologically induced positive shift - Tamanna Subba; Binita Pathak; Mukunda M. Gogoi; P. Ajay; Papori Dahutia; Aniket Chakraborty; Pradip K. Bhuyan (Atmospheric Environment, 2023)

Correction to: Wnt Signalling Inhibitors Potently Drive Trans-differentiation Potential of Mesenchymal Stem Cells Towards Neuronal Lineage - Antara Banerjee; Praveen Rowlo; Ganesan Jothimani; Asim K. Duttaroy; Surajit Pathak (Journal of Medical and Biological Engineering, 2023)

Energy and exergy analyses of fabricated pyramid type solar distillation plant for optimization: An experimental work - A. Geete; S. Rathore; V. K. Pathak (International Journal of Energy and Water Resources, 2023)

Nuclear architecture and the structural basis of mitotic memory - Mamilla Soujanya; Ashish Bihani; Nikhil Hajirnis; Rashmi U. Pathak; Rakesh K. Mishra (Chromosome Research, 2023)

Efficient removal of total arsenic (As3+/5+) from contaminated water by novel strategies mediated iron and plant extract activated waste flowers of marigold - Sudhir K. Upadhyay; Priyanka Devi; Vinay Kumar; Himanshu K. Pathak; Prasann Kumar; Vishnu D. Rajput; Padmanabh Dwivedi (Chemosphere, 2023)

Crop Residue Recycling Affecting Carbon Sequestration, Nutrients Availability and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat System - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak (Sugar Tech, 2023)

Reference genes selection for expression studies in Maconellicoccus hirsutus (Green) (Pseudococcidae: Hemiptera) under specific experimental conditions - K. V. Nagarjuna Reddy; Gandhi Gracy Ramasamy; Aditi Agrawal; Subhi Srivastava; Jyoti Pathak; Thiruvengadam Venkatesan; Dhanendra Kumar Rana (Molecular Biology Reports, 2023)

Decadal Changes in Atmospheric Methane Emissions in the Eastern Himalayan Region: Source Apportionment and Impact Assessment - Arshini Saikia; Binita Pathak; Praveen K. Singh; Pradip K. Bhuyan; Bhupesh Adhikary (International Journal of Environmental Research, 2023)

Development and validation of transient Thermal-Hydraulic model for SFR steam generators - G. Vikram; K. Natesan; M. Rajendrakumar; S.P. Pathak (Annals of Nuclear Energy, 2023)

Breeding for Drought Tolerance in Sugarcane: Indian Perspective - A. K. Mall; Varucha Misra; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2022)

Purification, characterization and assessment of stability, reactive oxygen species scavenging and antioxidative potentials of mycosporine-like amino acids (MAAs) isolated from cyanobacteria - Deepak K. Singh; Jainendra Pathak; Abha Pandey; Rajneesh; Vidya Singh; Rajeshwar P. Sinha (Journal of Applied Phycology, 2022)

Impact of Pollutant Load from Textile Dyeing Industry Wastewater on Biometric Growth Profile of Vigna radiata - Richa Kothari; Atin K. Pathak; Varsha Sharma; Shamshad Ahmad; Har Mohan Singh; Rajeev Pratap Singh; V. V. Tyagi (Bulletin of Environmental Contamination and Toxicology, 2022)

Improved Aerosolization Stability of Inhalable Tobramycin Powder Formulation by Co-Spray Drying with Colistin - Vaibhav Pathak; Heejun Park; Dmitry Zemlyanov; Sonal V. Bhujbal; Maizbha Uddin Ahmed; Mohammad A. K. Azad; Jian Li; Qi Tony Zhou (Pharmaceutical Research, 2022)

Irrigation water demand and elasticities: a case study of the High Plains aquifer - Santosh Pathak; Naveen C. Adusumilli; Hua Wang; Lal K. Almas (Irrigation Science, 2022)
The agriculture of the Texas High Plains (THP) region is primarily dependent on groundwater irrigation. Changing weather patterns along with competing demands for water resources and other anthropogenic effects have dramatically increased withdrawals from the Ogallala aquifer. In addition to on-farm changes, policy tools based on off-farm mechanisms are equally indispensable in addressing sustainable groundwater use in the THP. One such policy tool is water pricing using estimates of price elasticity of irrigation water demand. This paper estimates the elasticity of irrigation water demand in the THP and assesses the influence of water price on major inputs used in dominant irrigated crops such as corn and cotton. Using the translog profit function on an annual county-level dataset of THP crop production, spanning 23 years (1998–2020), we find that irrigation water demand is price elastic for cotton ( η = – 1.58) but inelastic for corn ( η = – 0.81). Our findings suggest that a non-uniform pricing policy could be a useful tool to promote the efficient use of groundwater for irrigation.

Climatology and model prediction of aerosol optical properties over the Indo-Gangetic Basin in north India - Amarendra Singh; Sumit Singh; A. K. Srivastava; Swagata Payra; Virendra Pathak; A. K. Shukla (Environmental Monitoring and Assessment, 2022)

A Comprehensive Cancer-Associated MicroRNA Expression Profiling and Proteomic Analysis of Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes - Ganesan Jothimani; Surajit Pathak; Suman Dutta; Asim K. Duttaroy; Antara Banerjee (Tissue Engineering and Regenerative Medicine, 2022)
Background: The mesenchymal stem cells (MSCs) have enormous therapeutic potential owing to their multi-lineage differentiation and self-renewal properties. MSCs express growth factors, cytokines, chemokines, and non-coding regulatory RNAs with immunosuppressive, anti-tumor, and migratory properties. MSCs also release several anti-cancer molecules via extracellular vesicles, that act as pro-apoptotic/tumor suppressor factors. This study aimed to identify the stem cell-derived secretome that could exhibit anti-cancer properties through molecular profiling of cargos in MSC-derived exosomes. Methods: Human umbilical cord mesenchymal stem cells (hUCMSCs) were isolated from umbilical cord tissues and culture expanded. Subsequently, exosomes were isolated from hUCMSC conditioned medium and characterized by DLS, electron microscopy. Western blot for exosome surface marker protein CD63 expression was performed. The miRNA profiling of hUCMSCs and hUCMSC-derived exosomes was performed, followed by functional enrichment analysis. Results: The tri-lineage differentiation potential, fibroblastic morphology, and strong expression of pluripotency genes indicated that isolated fibroblasts are MSCs. The isolated extracellular vesicles were 133.8 ± 42.49 nm in diameter, monodispersed, and strongly expressed the exosome surface marker protein CD63. The miRNA expression profile and gene ontology (GO) depicted the differential expression patterns of high and less-expressed miRNAs that are crucial to be involved in the regulation of apoptosis. The LCMS/MS data and GO analysis indicate that hUCMSC secretomes are involved in several oncogenic and inflammatory signaling cascades. Conclusion: Primary human MSCs released miRNAs and growth factors via exosomes that are increasingly implicated in intercellular communications, and hUCMSC-exosomal miRNAs have a critical influence in regulating cell death and apoptosis of cancer cells. Graphical abstract

Wnt Signalling Inhibitors Potently Drive Trans-differentiation Potential of Mesenchymal Stem Cells Towards Neuronal Lineage - Antara Banerjee; Praveen Rowlo; Ganesan Jothimani; Asim K. Duttaroy; Surajit Pathak (Journal of Medical and Biological Engineering, 2022)

Diversification Options in Sugarcane-Based Cropping Systems for Doubling Farmers’ Income in Subtropical India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. P. Dwivedi; S. K. Yadav; A. D. Pathak (Sugar Tech, 2022)

Nutrient Budget in Indian Agriculture During 1970–2018: Assessing Inputs and Outputs of Nitrogen, Phosphorus, and Potassium - H. Pathak; Ram K. Fagodiya (Journal of Soil Science and Plant Nutrition, 2022)

Relic surface water (clay-pore water) input triggers arsenic release into the shallow groundwater of Bengal aquifers - Pousali Pathak; Prosenjit Ghosh; Sanchita Banerjee; R S Chatterjee; Noor Muzakkira; Pradip K Sikdar; Utsab Ghosal; Mao-Chang Liang; Kathiravan Meeran (Journal of Earth System Science, 2022)

Species Composition and Diversity Dynamics of Actinomycetes in Arid and Semi-arid Salt Basins of Rajasthan - Khushbu Parihar; Praveen Gehlot; Manish Mathur; Alkesh Tak; Rakesh Pathak; Sunil K. Singh (Current Microbiology, 2022)

Fish community diversity assessment of protected Saraiyaman wetland in the Ganga River basin, India - Kripal Datt Joshi; Ajey Kumar Pathak; Santosh Kumar; Rajesh Dayal; Ajay Kumar Singh; Ravi Kumar; G. Kantharajan; Vindhya Mohindra; Kuldeep K. Lal (Community Ecology, 2022)

RNA-Seq analysis reveals the role of MYB12, MYB111 and MBW complex repressors in regulation of flavonoid biosynthesis in stigmas of saffron (Crocus sativus L.) flowers - Jyoti Pathak; Upasna Chettry; Nikhil K. Chrungoo; Arun B. Gurung (Acta Physiologiae Plantarum, 2022)

Screening and Optimization of Zinc Removal Potential in Pseudomonas aeruginosa-HMR1 and its Plant Growth-Promoting Attributes - Ali Asger Bhojiya; Harshada Joshi; Sudhir K. Upadhyay; Abhishek K. Srivastava; Vinayak Vandan Pathak; Vimal Chandra Pandey; Devendra Jain (Bulletin of Environmental Contamination and Toxicology, 2022)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Assessment of Groundwater Quality Index Using Geographic Information System in Parts of Rural Ajmer and Bhilwara Districts of Rajasthan, India - Swatantra K. Dubey; Sudhanshu K. Pathak; Devesh Sharma; Mukand S. Babel; Manish Kumar (Water Conservation Science and Engineering, 2021)

A review on interplay between small RNAs and oxidative stress in cancer progression - Aparimita Das; Harsha Ganesan; Sushmitha Sriramulu; Francesco Marotta; N. R. Rajesh Kanna; Antara Banerjee; Fang He; Asim K. Duttaroy; Surajit Pathak (Molecular and Cellular Biochemistry, 2021)

Partial purification of bacterial cellulo-xylanolytic enzymes and their application in deinking of photocopier waste paper - Chakarvati Sango; Puneet Pathak; Nishi K. Bhardwaj; Sunita Dalal; Jitender Sharma (Environmental Science and Pollution Research, 2021)

Spent marigold flower meal as an alternate feed for goats - Gagandeep Kour; R. K. Sharma; Nazam Khan; A. K. Pathak; Ankur Rastogi; Vijay Kumar Sharma (Tropical Animal Health and Production, 2021)

Management of Termites Through Different Tools and Their Impact on Environment and Soil Micro-arthropods in Sugarcane in Indo-Gangetic Plains of India - S. N. Sushil; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Identification of Appropriate Agri-technologies Minimizing Yield Gaps in Different Sugarcane-Growing States of India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; S. K. Awasthi; Adil Zubair; S. K. Yadav (Sugar Tech, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Potassium Influencing Physiological Parameters, Photosynthesis and Sugarcane Yield in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; Ishwar Singh; A. D. Pathak; Mona Nagargade; Arup Ghosh; C. Gupta; Asha Gaur; S. K. Awasthi; Raghvendra Tiwari; Abhay Srivastava; et al. (Sugar Tech, 2021)

Incidence and Diversity of Termites Associated with Sugarcane in North-West Zone of India with New Records - S. N. Sushil; C. M. Kalleshwaraswamy; M. Ranjith; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Sugarcane Yield Using Minimum Tillage Technology Through Subsoiling: Beneficial Impact on Soil Compaction, Carbon Conservation and Activity of Soil Enzymes - S. K. Shukla; V. P. Jaiswal; Lalan Sharma; A. D. Pathak; Akhilesh Kumar Singh; Rajendra Gupta; S. K. Awasthi; Asha Gaur; Adil Zubair; Raghvendra Tiwari (Sugar Tech, 2020)

Retraction Note: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2020)

Characterization of bioaerosols in Northeast India in terms of culturable biological entities along with inhalable, thoracic and alveolar particles - Binita Pathak; Debajit Borah; Ankita Khataniar; P K Bhuyan; A K Buragohain (Journal of Earth System Science, 2020)

Mapping of basement structure beneath the Kohima Synclinorium, north-east India via Bouguer gravity data modelling - Ch Ravi Kumar; N Kesiezie; B Pathak; Saumen Maiti; R K Tiwari (Journal of Earth System Science, 2020)

Spectral characteristics of talc and mineral abundance mapping in the Jahazpur Belt of Rajasthan, India using AVIRIS-NG data - B. K. Bhadra; Suparn Pathak; Dhruv Nanda; Ankit Gupta; S. Srinivasa Rao (International Journal of Remote Sensing, 2020)

Fish community and habitat diversity profiling of Luni, an ephemeral saline river from Thar Desert of India for conservation and management - Ajey Kumar Pathak; G. Kantharajan; V. P. Saini; Ravi Kumar; Rajesh Dayal; Vindhya Mohindra; Kuldeep K. Lal (Community Ecology, 2020)

Cyanobacterial Secondary Metabolite Scytonemin: A Potential Photoprotective and Pharmaceutical Compound - Jainendra Pathak; Abha Pandey; Pankaj K. Maurya; Rajneesh Rajneesh; Rajeshwar P. Sinha; Shailendra P. Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Cross genera transferability of microsatellite markers from other members of family Bignoniaceae to Tecomella undulata (Sm.) Seem - Rajwant K. Kalia; Sidhika Chhajer; Rakesh Pathak (Acta Physiologiae Plantarum, 2020)

Sequential treatment of paper mill effluent with modified Fenton oxidation and bioflocculation - Khanindra Sharma; Mihirjyoti Pathak; Suravi Kalita; K. G. Bhattacharyya; Neelotpal Sen Sarma; Arundhuti Devi (Environment, Development and Sustainability, 2020)

Physiological and Biochemical Response of a Hot-Spring Cyanobacterium Nostoc Sp. Strain HKAR-2 to Aluminum Toxicity - Vinod K. Kannaujiya; Deepak Kumar; Jainendra Pathak; Rajneesh; Rajeshwar P. Sinha (Water, Air, & Soil Pollution, 2020)

Functional variations between Mesenchymal Stem Cells of different tissue origins: A comparative gene expression profiling - K. N. Sangeetha; Rosy Vennila; R. Secunda; S. Sakthivel; Surajit Pathak; S. Jeswanth; R. Surendran (Biotechnology Letters, 2020)

Foliar Spray of Synthetic Osmolytes Alleviates Terminal Heat Stress in Late-Sown Wheat - A. Roy Chowdhury; M. Ghosh; M. Lal; A. Pal; K. K. Hazra; S. Acharya; A. Chaurasiya; S. K. Pathak (International Journal of Plant Production, 2020)

Determination of Morphological and Biochemical Basis of Resistance Against Top Borer, Scirpophaga excerptalis Walker in Sugarcane - S. N. Sushil; Amaresh Chandra; Sharmila Roy; A. K. Jaiswal; M. R. Singh; A. D. Pathak (Sugar Tech, 2020)

Investigations on diverse sesame (S. indicum L.) germplasm and its wild allies reveal wide variation in antioxidant potential - Niti Pathak; Neha Verma; Amrita Singh; K. V. Bhat; Suman Lakhanpaul (Physiology and Molecular Biology of Plants, 2020)

Photoprotective role of UV-screening pigment scytonemin against UV-B-induced damages in the heterocyst-forming cyanobacterium Nostoc sp. strain HKAR-2 - Abha Pandey; Jainendra Pathak; Deepak K. Singh; Haseen Ahmed; Vidya Singh; Deepak Kumar; Rajeshwar P. Sinha (Brazilian Journal of Botany, 2020)

The complete mitochondrial genome of Indian featherback Chitala chitala (Osteoglossiformes) and phylogenetic status - Rajeev K. Singh; Nimisha Dutta; Abhinav Pathak; Vindhya Mohindra; Gurjeet Kaur; Rajesh Kumar; R. S. Sah; J. K. Jena; Kuldeep K. Lal (Conservation Genetics Resources, 2019)

Impact of microphysics parameterizations and horizontal resolutions on simulation of “MORA” tropical cyclone over Bay of Bengal using Numerical Weather Prediction Model - Lakhima Chutia; Binita Pathak; Ajay Parottil; P. K. Bhuyan (Meteorology and Atmospheric Physics, 2019)

Inflammation and breast density among female Chinese immigrants: exploring variations across neighborhoods - Carolyn Y. Fang; Brian L. Egleston; Celia Byrne; Gregory S. Bohr; Harsh B. Pathak; Andrew K. Godwin; Philip T. Siu; Marilyn Tseng (Cancer Causes & Control, 2019)

Historic migration to South Asia in the last two millennia: A case of Jewish and Parsi populations - Ajai K Pathak; Anshika Srivastava; Prajjval Pratap Singh; Debashruti Das; Audditiya Bandopadhyay; Pooja Singh; Gyaneshwer Chaubey (Journal of Biosciences, 2019)

Obtaining best parameterization scheme of RegCM 4.4 for aerosols and chemistry simulations over the CORDEX South Asia - P. Ajay; B. Pathak; F. Solmon; P. K. Bhuyan; F. Giorgi (Climate Dynamics, 2019)

Identification of resistance in cultivated and wild bitter gourd against root knot nematode, Meloidogyne incognita - Renu Sharma; Sukhjeet Kaur; N. K. Dhillon; Mamta Pathak (Indian Phytopathology, 2019)

Meta-analysis of genomic variants and gene expression data in schizophrenia suggests the potential need for adjunctive therapeutic interventions for neuropsychiatric disorders - S. Anirudh Chellappa; Ankit Kumar Pathak; Prashant Sinha; ASHWIN K. Jainarayanan; Sanjeev Jain; Samir K. Brahmachari (Journal of Genetics, 2019)

Kinetics of Total Volatile Basic Nitrogen and Trimethylamine Formation in Stored Rohu ( Labeo rohita ) Fish - Pramod K. Prabhakar; Prem P. Srivastav; Sant S. Pathak (Journal of Aquatic Food Product Technology, 2019)

Green Technologies for Improving Cane Sugar Productivity and Sustaining Soil Fertility in Sugarcane-Based Cropping System - S. K. Shukla; S. Solomon; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; Priyanka Singh (Sugar Tech, 2019)

Tinospora cordifolia Suppresses Neuroinflammation in Parkinsonian Mouse Model - Hareram Birla; Sachchida Nand Rai; Saumitra Sen Singh; Walia Zahra; Arun Rawat; Neeraj Tiwari; Rakesh K. Singh; Abhishek Pathak; Surya Pratap Singh (NeuroMolecular Medicine, 2019)

Deciphering the transcriptome of prepubertal buffalo mammary glands using RNA sequencing - Ratan K. Choudhary; Shanti Choudhary; C. S. Mukhopadhyay; Devendra Pathak; Ramneek Verma (Functional & Integrative Genomics, 2019)

Impact of Temperature and Humidity on Sugar Recovery in Uttar Pradesh - S. K. Pathak; Priyanka Singh; M. M. Singh; B. L. Sharma (Sugar Tech, 2019)

Microsatellite marker set for genetic diversity assessment of primitive Chitala chitala (Hamilton, 1822) derived through SMRT sequencing technology - Nimisha Dutta; Rajeev K. Singh; Vindhya Mohindra; Abhinav Pathak; Raj Kumar; Priyanka Sah; Sangeeta Mandal; Gurjeet Kaur; Kuldeep K. Lal (Molecular Biology Reports, 2019)

Ecosystem services in different agro-climatic zones in eastern India: impact of land use and land cover change - Rahul Tripathi; K. C. Moharana; A. D. Nayak; B. Dhal; Md Shahid; B. Mondal; S. D. Mohapatra; P. Bhattacharyya; Nuala Fitton; Pete Smith; A. K. Shukla; H. Pathak; et al. (Environmental Monitoring and Assessment, 2019)

Understanding the role of moisture transport on the dry bias in indian monsoon simulations by CFSv2 - A. S. Sahana; Amey Pathak; M. K. Roxy; Subimal Ghosh (Climate Dynamics, 2019)

Laser-induced breakdown spectroscopy (LIBS): a novel technology for identifying microbes causing infectious diseases - Vivek K. Singh; Jitendra Sharma; Ashok K. Pathak; Charles T. Ghany; M. A. Gondal (Biophysical Reviews, 2018)

Impact of seasonal thermal stress on physiological and blood biochemical parameters in pigs under different dietary energy levels - P. K. Pathak; R. Roychoudhury; J. Saharia; M. C. Borah; D. J. Dutta; R. Bhuyan; D. Kalita (Tropical Animal Health and Production, 2018)

Composition and functional property of photosynthetic pigments under circadian rhythm in the cyanobacterium Spirulina platensis - Deepak Kumar; Vinod K. Kannaujiya; Richa; Jainendra Pathak; Shanthy Sundaram; Rajeshwar P. Sinha (Protoplasma, 2018)

Application of BICOVOX catalyst for hydrogen production from ethanol - S. Sharma; B. Patil; A. Pathak; S. Ghosalkar; H. K. Mohanta; B. Roy (Clean Technologies and Environmental Policy, 2018)

Immunolocalization of Musashi1 and Fibronectin Type III Domain Containing 3B in Water Buffalo Mammary Glands - Harmanjot Kaur; Shanti Choudhary; Devendra Pathak; Opinder Singh; Ramneek Verma; Ratan K. Choudhary (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Soil microbial responses as influenced by Jatropha plantation under rainfed condition in north-west India - Ahmad Mahmoud; S. D. Singh; K. S. Muralikrishna; H. Pathak; Namita Das Saha (Agroforestry Systems, 2018)

Camel Milk: An Important Natural Adjuvant - Raghvendar Singh; Gorakh Mal; Devendra Kumar; N. V. Patil; K. M. L. Pathak (Agricultural Research, 2017)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)

In Silico Drug-Designing Studies on Flavanoids as Anticolon Cancer Agents: Pharmacophore Mapping, Molecular Docking, and Monte Carlo Method-Based QSAR Modeling - Lalitha Simon; Abdelli Imane; K. K. Srinivasan; Lokesh Pathak; I. Daoud (Interdisciplinary Sciences: Computational Life Sciences, 2017)

RNA Seq analysis for transcriptome profiling in response to classical swine fever vaccination in indigenous and crossbred pigs - Shalu Kumari Pathak; Amit Kumar; G. Bhuwana; Vaishali Sah; Vikramadiya Upmanyu; A. K. Tiwari; A. P. Sahoo; A. R. Sahoo; Sajjad A. Wani; Manjit Panigrahi; N. R. Sahoo; Ravi Kumar (Functional & Integrative Genomics, 2017)

Impact of High Sugar Early Maturing Varieties for Sustainable Sugar Production in SubTropical India - Priyanka Singh; S. K. Pathak; M. M. Singh; V. Mishra; B. L. Sharma (Sugar Tech, 2017)

Soil Carbon Sequestration and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat Cropping Systems Through Crop Residue Management and Inoculation of Trichoderma viride in Subtropical India - S. K. Shukla; Swaha Shee; S. K. Maity; S. Solomon; S. K. Awasthi; Asha Gaur; A. D. Pathak; V. P. Jaiswal (Sugar Tech, 2017)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)
In order to understand the climatic implications of atmospheric aerosols, top of atmosphere ( TOA ) shortwave ( SW , 0.3–5 µm) fluxes and aerosol optical depth ( AOD ) at 550 nm retrieved simultaneously by clouds and the earth's radiant energy system ( CERES ) and moderate resolution imaging spectroradiometer ( MODIS ) instruments, respectively, are analysed over North‐East India and its adjoining areas for the period July 2002–December 2013. The aerosol‐free TOA flux obtained by establishing the linear regression between CERES SW TOA fluxes and MODIS AODs exhibits strong seasonality with peak values in monsoon and minimum in winter. Same seasonality is captured by the Santa Barbara DISORT Atmospheric Radiative Transfer ( SBDART ) model, but with difference in absolute values. SBDART code is used to extend instantaneous radiative forcing estimates into 24‐h averages. AOD over the North East India region with complex terrain shows altitudinal variation with maximum value at the lowest elevation site Dhaka and minimum value at the high‐altitude locations Shillong and Aizwal. In general, strong seasonality in AOD is observed with a peak in pre‐monsoon (March–May) and dip in post‐monsoon (October–November) at all the locations. The direct instantaneous TOA shortwave aerosol radiative forcing ( SWARF ) shows maximum values in pre‐monsoon over all the locations except at Guwahati, Banmauk, Aizawl, and Shillong. The lowest value of instantaneous SWARF is observed in post‐monsoon except at Banmauk and Shillong. Climatologically TOA diurnally averaged SWARF varies between −6.95 W m −2 in Aizawl to −20.39 W m −2 in Shillong. In general, the TOA SW forcing efficiency is highest in monsoon at all the locations. The radiative forcing efficiency is found to be less negative when surface reflectance increases.

Elevational distribution of butterflies in the Himalayas: a case study from Langtang National Park, Nepal - Ranjit Pandey; Kapil K. Khadka; Anuj Ghimire; Puja Jha; Umesh Pathak (Journal of Mountain Science, 2017)

Simulation of leaf blast infection in tropical rice agro-ecology under climate change scenario - K. Viswanath; P. Sinha; S. Naresh Kumar; Taru Sharma; Shalini Saxena; Shweta Panjwani; H. Pathak; Shalu Mishra Shukla (Climatic Change, 2017)

Control of campylobacter in poultry industry from farm to poultry processing unit: A review - Pramila Umaraw; A. Prajapati; Akhilesh K. Verma; V. Pathak; V. P. Singh (Critical Reviews in Food Science and Nutrition, 2017)

Weed and Nitrogen Management Effects on Weed Infestation and Crop Productivity of Wheat–Mungbean Sequence in Conventional and Conservation Tillage Practices - C. P. Nath; T. K. Das; K. S. Rana; R. Bhattacharyya; H. Pathak; S. Paul; M. C. Meena; S. B. Singh (Agricultural Research, 2017)

Genetic diversity of Indian jujube cultivars using SCoT, ISSR, and rDNA markers - S. K. Singh; Sidhika Chhajer; Rakesh Pathak; R. K. Bhatt; Rajwant K. Kalia (Tree Genetics & Genomes, 2017)

Crop Diversification Options Involving Pulses and Sugarcane for Improving Crop Productivity, Nutritional Security and Sustainability in India - S. K. Shukla; K. K. Singh; A. D. Pathak; V. P. Jaiswal; S. Solomon (Sugar Tech, 2017)

Habitat Fingerprinting Using Otolith Trace Metal Profile of Two Catfish Species of Genus Ompok (Siluridae) from Ganges Basin, India - U. K. Sarkar; A. K. Pathak; B. K. Gupta; D. D. Patra (Proceedings of the Zoological Society, 2016)

In Vitro Antibacterial Activity of Ethno Medicinally Used Lichens Against Three Wound Infecting Genera of Enterobacteriaceae - Ashutosh Pathak; Shashi Kant Shukla; Anand Pandey; Rohit K. Mishra; Rajesh Kumar; Anupam Dikshit (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

The Vitamin E Analog Gamma-Tocotrienol (GT3) Suppresses Radiation-Induced Cytogenetic Damage - Rupak Pathak; Abdel Bachri; Sanchita P. Ghosh; Igor Koturbash; Marjan Boerma; Regina K. Binz; Jeffrey R. Sawyer; Martin Hauer-Jensen (Pharmaceutical Research, 2016)

Influence of varying nitrogen levels on lipid accumulation in Chlorella sp. - B. Kiran; K. Pathak; R. Kumar; D. Deshmukh; N. Rani (International Journal of Environmental Science and Technology, 2016)

Super-Optimal NPK Along with Foliar Iron Application Influences Bioavailability of Iron and Zinc of Wheat - Rajiv Rakshit; A. K. Patra; T. J. Purakayastha; R. D. Singh; H. Pathak; Shiva Dhar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

The Stress of Suicide: Temporal and Spatial Expression of Putative Heat Shock Protein 70 Protect the Cells from Heat Injury in Wheat (Triticum aestivum) - Ranjeet R. Kumar; Suneha Goswami; Richa Gupta; Pooja Verma; Khushboo Singh; Jyoti P. Singh; Mahesh Kumar; Sushil K. Sharma; Himanshu Pathak; Raj D. Rai (Journal of Plant Growth Regulation, 2016)

Analysis of trends in streamflow and its linkages with rainfall and anthropogenic factors in Gomti River basin of North India - N. S. Abeysingha; Man Singh; V. K. Sehgal; Manoj Khanna; Himanshu Pathak (Theoretical and Applied Climatology, 2016)

De novo development and characterization of polymorphic microsatellite markers in a schilbid catfish, Silonia silondia (Hamilton, 1822) and their validation for population genetic studies - Sangeeta Mandal; J. K. Jena; Rajeev K. Singh; Vindhya Mohindra; W. S. Lakra; Geetanjali Deshmukhe; Abhinav Pathak; Kuldeep K. Lal (Molecular Biology Reports, 2016)

Molecular Characterization of Commercial Varieties of Phyllanthus emblica Using RAPD and Nuclear rDNA SNPs - S. K. Singh; P. R. Meghwal; Rakesh Pathak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Calcium triggers protein kinases-induced signal transduction for augmenting the thermotolerance of developing wheat (Triticum aestivum) grain under the heat stress - Suneha Goswami; Ranjeet R. Kumar; Sushil K. Sharma; Yugal K. Kala; Khushboo Singh; Richa Gupta; Gaurav Dhavan; Gyanendra K. Rai; Gyanendra P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2015)

Development of GIS-based fuzzy pattern recognition model (modified DRASTIC model) for groundwater vulnerability to pollution assessment - J. Iqbal; A. K. Gorai; Y. B. Katpatal; G. Pathak (International Journal of Environmental Science and Technology, 2015)

Cost-Effective Cultivation of Spirulina platensis Using NPK Fertilizer - Ankita Kumari; Akhilendra K. Pathak; Chandan Guria (Agricultural Research, 2015)

Salicylic acid alleviates the heat stress-induced oxidative damage of starch biosynthesis pathway by modulating the expression of heat-stable genes and proteins in wheat (Triticum aestivum) - Ranjeet R. Kumar; Sushil K. Sharma; Suneha Goswami; Pooja Verma; Khushboo Singh; Nidhi Dixit; Himanshu Pathak; C. Viswanathan; Raj D. Rai (Acta Physiologiae Plantarum, 2015)

Accumulation of heavy metals in the vegetables grown in wastewater irrigated areas of Dehradun, India with reference to human health risk - A. K. Chopra; Chakresh Pathak (Environmental Monitoring and Assessment, 2015)

Development of hierarchical fuzzy model for groundwater vulnerability to pollution assessment - Jawed Iqbal; Gopal Pathak; A. K. Gorai (Arabian Journal of Geosciences, 2015)

Moisture stable heteroleptic titanium (IV) complexes derived from 8-hydroxyquinoline: synthesis, antibacterial, and antifungal studies - Blassan Samuel; K. R. Ethiraj; Madhvesh Pathak (Medicinal Chemistry Research, 2015)

Anti-inflammatory and chondroprotective effects of atorvastatin in a cartilage explant model of osteoarthritis - Nitya N. Pathak; Madhu C. Lingaraju; Venkanna Balaganur; Vinay Kant; Amar S. More; Dhirendra Kumar; Dinesh Kumar; Surendra K. Tandan (Inflammation Research, 2015)

Physicochemical and toxicological characterization of sucrose-bound polynuclear iron oxyhydroxide formulations - Bhavesh S. Barot; Punit B. Parejiya; Pragna K. Shelat; Gaurang B. Shah; Dharmik M. Mehta; Trupti V. Pathak (Journal of Pharmaceutical Investigation, 2015)

Homology Modeling and Comparative Profiling of Superoxide Dismutase Among Extremophiles: Exiguobacterium as a Model Organism - Rajiv Pathak; Pankaj Narang; Muktesh Chandra; Raj Kumar; P. K. Sharma; Hemant K. Gautam (Indian Journal of Microbiology, 2014)

Assessment of Genetic Diversity Among Indian Jujube Varieties Based on Nuclear Ribosomal DNA and RAPD Polymorphism - S. K. Singh; P. R. Meghwal; Rakesh Pathak; R. K. Bhatt; Ragini Gautam (Agricultural Research, 2014)

Ascorbic acid at pre-anthesis modulate the thermotolerance level of wheat (Triticum aestivum) pollen under heat stress - Ranjeet R. Kumar; Suneha Goswami; Kritika A. Gadpayle; Khushboo Singh; Sushil K. Sharma; G. P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2014)

Ammonia Emission from Rice–Wheat Cropping System in Subtropical Soil of India - S. K. Sharma; R. C. Harit; V. Kumar; T. K. Mandal; H. Pathak (Agricultural Research, 2014)

Infections do not predict shedding in co‐infections with two helminths from a natural system - Isabella M. Cattadori; Benjamin R. Wagner; Laura A. Wodzinski; Ashutosh K. Pathak; Adam Poole; Brian Boag (Ecology, 2014)
Given the health and economic burden associated with the widespread occurrence of co‐infections in humans and agricultural animals, understanding how co‐infections contribute to host heterogeneity to infection and transmission is critical if we are to assess risk of infection based on host characteristics. Here, we examine whether host heterogeneity to infection leads to similar heterogeneity in transmission in a population of rabbits single and co‐infected with two helminths and monitored monthly for eight years. Compared to single infections, co‐infected rabbits carried higher Trichostrongylus retortaeformis intensities, shorter worms with fewer eggs in utero, and shed similar numbers of parasite eggs. In contrast, the same co‐infected rabbits harbored fewer Graphidium strigosum with longer bodies and more eggs in utero, and shed more eggs of this helminth. A positive density‐dependent relationship between fecundity and intensity was found for T. retortaeformis but not G. strigosum in co‐infected rabbits. Juvenile rabbits contributed to most of the infection and shedding of T. retortaeformis , while adult hosts were more important for G. strigosum dynamics of infection and transmission, and this pattern was consistent in single and co‐infected individuals. This host–parasite system suggests that we cannot predict the pattern of parasite shedding during co‐infections based on intensity of infection alone. We suggest that a mismatching between susceptibility and infectiousness should be expected in helminth co‐infections and should not be overlooked.

Association studies of dormancy and cooking quality traits in direct-seeded indica rice - SUNAYANA RATHI; K. PATHAK; R. N. S. YADAV; B. KUMAR; R. N. SARMA (Journal of Genetics, 2014)

Exploring QSAR studies on 4-substituted quinazoline derivatives as antimalarial compounds for the development of predictive models - Mitali Mishra; Vikash Kumar Mishra; Parul Senger; Anupam Kumar Pathak; Sushil K. Kashaw (Medicinal Chemistry Research, 2014)

Genome-wide identification and expression analysis of the mitogen-activated protein kinase gene family from banana suggest involvement of specific members in different stages of fruit ripening - Mehar Hasan Asif; Deepika Lakhwani; Sumya Pathak; Sweta Bhambhani; Sumit K. Bag; Prabodh Kumar Trivedi (Functional & Integrative Genomics, 2014)

Impairment of Mitochondrial–Nuclear Cross Talk in Neutrophils of Patients with Type 2 Diabetes Mellitus - Saba Khan; Gorantla V. Raghuram; Neelam Pathak; Subodh K. Jain; Dolly H. Chandra; Pradyumna K. Mishra (Indian Journal of Clinical Biochemistry, 2014)

Characterization of smallholder pig production system: productive and reproductive performances of local and crossbred pigs in Sikkim Himalayan region - B. G. Nath; P. K. Pathak; S. V. Ngachan; A. K. Tripathi; A. K. Mohanty (Tropical Animal Health and Production, 2013)

Trends and fluctuations of rainfall regime in the Brahmaputra and Barak basins of Assam, India - R. L. Deka; C. Mahanta; H. Pathak; K. K. Nath; S. Das (Theoretical and Applied Climatology, 2013)

QSAR studies of novel potent benzamide derivatives as glucokinase activators - Nimisha Jain; Anand B. Mundada; Anupam K. Pathak (Medicinal Chemistry Research, 2013)

Accumulation of heavy metals in Spinacia oleracea irrigated with paper mill effluent and sewage - Chakresh Pathak; A. K. Chopra; Sachin Srivastava (Environmental Monitoring and Assessment, 2013)

Agro-potentiality of distillery effluent on soil and agronomical characteristics of Abelmoschus esculentus L. (okra) - A. K. Chopra; Sachin Srivastava; Vinod Kumar; Chakresh Pathak (Environmental Monitoring and Assessment, 2013)

ASTER Data Analysis for Mineral Potential Mapping Around Sawar-Malpura Area, Central Rajasthan - B. K. Bhadra; Suparn Pathak; G. Karunakar; J. R. Sharma (Journal of the Indian Society of Remote Sensing, 2013)

Cross-Species Induction and Enhancement of Antimicrobial Properties in Response to Gamma Irradiation in Exiguobacterium sp. HKG 126 - Rajiv Pathak; Raj Kumar; Hemant K. Gautam (Indian Journal of Microbiology, 2013)

Biodiversity in wood-decay macro-fungi associated with declining arid zone trees of India as revealed by nuclear rDNA analysis - S. K. Singh; Anila Doshi; Anjly Pancholy; Rakesh Pathak (European Journal of Plant Pathology, 2013)

Decreased expression of DNA repair genes (XRCC1, ERCC1, ERCC2, and ERCC4) in squamous intraepithelial lesion and invasive squamous cell carcinoma of the cervix - Deepti Bajpai; Ayan Banerjee; Sujata Pathak; Sunesh K. Jain; Neeta Singh (Molecular and Cellular Biochemistry, 2013)

Enrichment and Translocation of Heavy Metals in Soil and Spinacea oleracea Grown in Sugar Mill Effluent Irrigated Soil - A. K. Chopra; Chakresh Pathak (Sugar Tech, 2013)

Class Separability Analysis and Classifier Comparison using Quad-polarization Radar Imagery - Manoj Joseph; S. Rama Subramoniam; K. S. Srinivasan; Suparn Pathak; J. R. Sharma (Journal of the Indian Society of Remote Sensing, 2013)

Particulate matter concentration in ambient air and its effects on lung functions among residents in the National Capital Region, India - C. Kesavachandran; B. S. Pangtey; V. Bihari; M. Fareed; M. K. Pathak; A. K. Srivastava; N. Mathur (Environmental Monitoring and Assessment, 2013)

Differential expression of heat shock protein and alteration in osmolyte accumulation under heat stress in wheat - Ranjeet R. Kumar; Suneha Goswami; Sushil K. Sharma; Khushboo Singh; Kritika A. Gadpayle; S. D. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2013)

Development of fuzzy air quality index using soft computing approach - T. Mandal; A. K. Gorai; G. Pathak (Environmental Monitoring and Assessment, 2012)

Pyridoquinolones containing azetidinones: synthesis and their biological evaluation - Navin B. Patel; Kunal K. Pathak (Medicinal Chemistry Research, 2012)

Ammonia emission from subtropical crop land area in India - A. Datta; S. K. Sharma; R. C. Harit; V. Kumar; T. K. Mandal; H. Pathak (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Evaluation of bactericidal efficacy of silver ions on Escherichia coli for drinking water disinfection - Satya P. Pathak; K. Gopal (Environmental Science and Pollution Research, 2012)

Bioaccumulation and Translocation Efficiency of Heavy Metals in Vegetables Grown on Long-Term Wastewater Irrigated Soil Near Bindal River, Dehradun - A. K. Chopra; Chakresh Pathak (Agricultural Research, 2012)

Greenhouse gas mitigation in rice–wheat system with leaf color chart-based urea application - Arti Bhatia; Himanshu Pathak; Niveta Jain; Pawan K. Singh; Ritu Tomer (Environmental Monitoring and Assessment, 2012)

Freshwater fish biodiversity in the River Ganga (India): changing pattern, threats and conservation perspectives - U. K. Sarkar; A. K. Pathak; R. K. Sinha; K. Sivakumar; A. K. Pandian; A. Pandey; V. K. Dubey; W. S. Lakra (Reviews in Fish Biology and Fisheries, 2012)

Molecular characterization of Vigna radiata (L.) Wilczek genotypes based on nuclear ribosomal DNA and RAPD polymorphism - Aparna Raturi; S. K. Singh; Vinay Sharma; Rakesh Pathak (Molecular Biology Reports, 2012)

Genome-wide transcriptomic analysis of cotton under drought stress reveal significant down-regulation of genes and pathways involved in fibre elongation and up-regulation of defense responsive genes - Kethireddy Venkata Padmalatha; Gurusamy Dhandapani; Mogilicherla Kanakachari; Saravanan Kumar; Abhishek Dass; Deepak Prabhakar Patil; Vijayalakshmi Rajamani; Krishan Kumar; Ranjana Pathak; Bhupendra Rawat; Sadhu Leelavathi; Palakolanu Sudhakar Reddy; et al. (Plant Molecular Biology, 2012)

Studies on urban drinking water quality in a tropical zone - Mohana Krishna Reddy Mudiam; S. P. Pathak; K. Gopal; R. C. Murthy (Environmental Monitoring and Assessment, 2012)

QSAR analysis of Mur B inhibitors with antibacterial properties discussing role of physico-chemical parameters - A. K. Srivastava; Vinay Kumar Pathak; Archana; Meetu Jaiswala; Vijay K. Agrawal (Medicinal Chemistry Research, 2011)

Supplementation of zinc mitigates the altered uptake and turnover of 65Zn in liver and whole body of diabetic rats - Ashima Pathak; Vishawjyoti Sharma; Sanjeev Kumar; D. K. Dhawan (BioMetals, 2011)

GPS based TEC measurements for a period August 2008– December 2009 near the northern crest of Indian equatorial ionospheric anomaly region - S P KARIA; K N PATHAK (Journal of Earth System Science, 2011)

Ameliorating effect of N-acetylcysteine and curcumin on pesticide-induced oxidative DNA damage in human peripheral blood mononuclear cells - Tanzeel Ahmed; Rahul Pathak; MD. Mustafa; Rajarshi Kar; Ashok K. Tripathi; Rafat S. Ahmed; B. D. Banerjee (Environmental Monitoring and Assessment, 2011)

Erratum to: Genome-wide transcriptome and proteome analyses of tobacco psaA and psbA deletion mutants - Sadhu Leelavathi; Amit Bhardwaj; Saravanan Kumar; Abhishek Dass; Ranjana Pathak; Shiv S. Pandey; Baishnab C. Tripathy; K. V. Padmalatha; Gurusamy Dhandapani; Mogilicherla Kanakachari; Amolkumar Uddhaorao Solanke; Polumetla Ananda Kumar; et al. (Plant Molecular Biology, 2011)

Genome-wide transcriptome and proteome analyses of tobacco psaA and psbA deletion mutants - Sadhu Leelavathi; Amit Bhardwaj; Saravanan Kumar; Abhishek Dass; Ranjana Pathak; Shiv S. Pandey; Baishnab C. Tripathy; K. V. Padmalatha; Gurusamy Dhandapani; Mogilicherla Kanakachari; Polumetla Ananda Kumar; Rino Cella; et al. (Plant Molecular Biology, 2011)

Assessment of Genetic Diversity in Trigonella foenum-graecum Based on Nuclear Ribosomal DNA, Internal Transcribed Spacer and RAPD Analysis - R. K. Kakani; S. K. Singh; Anjly Pancholy; R. S. Meena; Rakesh Pathak; Aparna Raturi (Plant Molecular Biology Reporter, 2011)

Circulating Biomarkers and their Possible Role in Pathogenesis of Chronic Hepatitis B and C Viral Infections - Saba Khan; Arpit Bhargava; Neelam Pathak; Kewal. K. Maudar; Subodh Varshney; Pradyumna K. Mishra (Indian Journal of Clinical Biochemistry, 2011)

Genetic and non-genetic factors affecting semen production traits in Karan Fries crossbred bulls - Indra Sen Chauhan; Ashok K. Gupta; Keviletsu Khate; Anuj Chauhan; Thakur Krishna Shankar Rao; Shivendra Pathak; Ritwik Hazra; Maneesh Singh (Tropical Animal Health and Production, 2010)

Genomic mapping and testing for quantitative trait loci in tea (Camellia sinensis (L.) O. Kuntze) - S. M. Kamunya; F. N. Wachira; R. S. Pathak; R. Korir; V. Sharma; R. Kumar; P. Bhardwaj; R. Chalo; P. S. Ahuja; R. K. Sharma (Tree Genetics & Genomes, 2010)

Maternal and cord blood levels of Aldrin and Dieldrin in Delhi population - MD. Mustafa; Rahul Pathak; A. K. Tripathi; Rafat S. Ahmed; Kiran Guleria; B. D. Banerjee (Environmental Monitoring and Assessment, 2010)

Intake and utilization of sorghum and maize green fodder in spotted deer under captivity - A. Sahoo; A. K. Garg; B. M. Arora; N. N. Pathak (Tropical Animal Health and Production, 2010)

Complete nucleotide sequence of the envelope gene of pseudocowpox virus isolates from Indian dromedaries (Camelus dromedarius) - G. Nagarajan; S. K. Ghorui; Sanjay Kumar; K. M. L. Pathak (Archives of Virology, 2010)

Characterization of 2T engine oil degrading indigenous bacteria, isolated from high altitude (Mussoorie), India - Pankaj Kumar Jain; Vijai K. Gupta; Hardik Pathak; Madan Lowry; D. P. Jaroli (World Journal of Microbiology and Biotechnology, 2010)

Isolation and characterization of Indian isolates of camel pox virus - V. Bhanuprakash; V. Balamurugan; M. Hosamani; G. Venkatesan; Bina Chauhan; V. A. Srinivasan; R. S. Chauhan; K. M. L. Pathak; Raj Kumar Singh (Tropical Animal Health and Production, 2010)

Molecular assessment of genetic diversity in cluster bean (Cyamopsis tetragonoloba) genotypes - Rakesh Pathak; S. K. Singh; Manjit Singh; A. Henry (Journal of Genetics, 2010)

Soil–plant–animal continuum in relation to macro and micro mineral status of dairy cattle in subtropical hill agro ecosystem - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Brajendra; T. Ramesh (Tropical Animal Health and Production, 2010)

Trade-off between productivity enhancement and global warming potential of rice and wheat in India - A. Bhatia; H. Pathak; P. K. Aggarwal; N. Jain (Nutrient Cycling in Agroecosystems, 2010)

Diagnosis of gastrointestinal tuberculosis: Using cytomorphological, microbiological, immunological and molecular techniques — A study from Central India - Pradyumna Kumar Mishra; A. Bhargava; R. P. Punde; N. Pathak; P. Desikan; A. Jain; S. Varshney; K. K. Maudar (Indian Journal of Clinical Biochemistry, 2010)

Role of nodD gene product and flavonoid interactions in induction of nodulation genes in Mesorhizobium ciceri - D. V. Kamboj; Ranjana Bhatia; D. V. Pathak; P. K. Sharma (Physiology and Molecular Biology of Plants, 2010)

Segment-2 sequence analysis and cross-neutralization studies on some Indian bluetongue viruses suggest isolates are VP2-variants of serotype 23 - Prabhakar A. Tembhurne; Bimalendu Mondal; Kunj B. Pathak; Sanchay K. Biswas; Aniket Sanyal; Mahendra P. Yadav; Santanu K. Bandyopadhyay; Raj K. Singh (Archives of Virology, 2010)

Integrated resource-driven pig production systems in a mountainous area of Northeast India: production practices and pig performance - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Anubrata Das; R. K. Bardoloi (Tropical Animal Health and Production, 2009)

Eco-restoration of a high-sulphur coal mine overburden dumping site in northeast India: A case study - J. Dowarah; H. P. Deka Boruah; J. Gogoi; N. Pathak; N. Saikia; A. K. Handique (Journal of Earth System Science, 2009)

Mineral profiling of local pig-feeds and pigs reared under resource driven production system to reduce porcine mineral deficiency in subtropical hill ecosystem of Northeastern India - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Anubrata Das; T. Ramesh (Tropical Animal Health and Production, 2009)

Genomewide bioinformatic analysis negates any specific role for Dof, GATA and Ag/cTCA motifs in nitrate responsive gene expression in Arabidopsis - Ravi Ramesh Pathak; Suman K. Das; Devapriya Choudhury; Nandula Raghuram (Physiology and Molecular Biology of Plants, 2009)

Analysis of integrated animal-fish production system under subtropical hill agro ecosystem in India: Growth performance of animals, total biomass production and monetary benefit - A. Kumaresan; K. A. Pathak; K. M. Bujarbaruah; K. Vinod (Tropical Animal Health and Production, 2009)

Reproductive performance of crossbred dairy cows reared under traditional low input production system in the eastern Himalayas - A. Kumaresan; P. P. Prabhakaran; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed (Tropical Animal Health and Production, 2009)

Effect of growth regulators on in vitro multiplication and rooting of shoot cultures in sugarcane - Shweta Pathak; M. Lal; A. K. Tiwan; M. L. Sharma (Sugar Tech, 2009)

Site-specific nutrient management in rice in Eastern India using a modeling approach - D. K. Das; Debtanu Maiti; H. Pathak (Nutrient Cycling in Agroecosystems, 2009)

Distribution of vehicular pollutants in street canyons of Varanasi, India: a different case - Santosh K. Prajapati; B. D. Tripathi; Vinita Pathak (Environmental Monitoring and Assessment, 2009)

Queuine mediated inhibition in phosphorylation of tyrosine phosphoproteins in cancer - Chandramani Pathak; Yogesh K. Jaiswal; Manjula Vinayak (Molecular Biology Reports, 2008)

Enhancement in alpha-tocopherol succinate-induced apoptosis by all-trans-retinoic acid in primary leukemic cells: role of antioxidant defense, Bax and c-myc - K. L. Khanduja; S. Kumar; N. Varma; S. C. Varma; P. K. Avti; C. M. Pathak (Molecular and Cellular Biochemistry, 2008)

Reproductive pathways of seed development in apomictic guinea grass (Panicum maximum Jacq.) reveal uncoupling of apomixis components - P. Kaushal; D. R. Malaviya; A. K. Roy; Shalini Pathak; A. Agrawal; Ambica Khare; S. A. Siddiqui (Euphytica, 2008)

Queuine mediated inhibition in phosphorylation of tyrosine phosphoproteins in cancer - Chandramani Pathak; Yogesh K. Jaiswal; Manjula Vinayak (Molecular Biology Reports, 2008)

Conservation of freshwater fish resources of India: new approaches, assessment and challenges - U. K. Sarkar; A. K. Pathak; W. S. Lakra (Biodiversity and Conservation, 2008)

Analysis of a village chicken production system and performance of improved dual purpose chickens under a subtropical hill agro-ecosystem in India - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed; Santosh Haunshi (Tropical Animal Health and Production, 2008)

Endosulfan and Other Organochlorine Pesticide Residues in Maternal and Cord Blood in North Indian Population - Rahul Pathak; Sanvidhan G. Suke; Rafat S. Ahmed; A. K. Tripathi; Kiran Guleria; C. S. Sharma; S. D. Makhijani; Meenu Mishra; B. D. Banerjee (Bulletin of Environmental Contamination and Toxicology, 2008)

Modified Polysaccharides as Fast Disintegrating Excipients for Orodispersible Tablets of Roxithromycin - Vijay Sharma; Anil K. Philip; Kamla Pathak (AAPS PharmSciTech, 2008)

Optimization Studies on Design and Evaluation of Orodispersible Pediatric Formulation of Indomethacin - Jashanjit Singh; Anil K. Philip; Kamla Pathak (AAPS PharmSciTech, 2008)

Genomewide computational analysis of nitrate response elements in rice and Arabidopsis - Suman K. Das; Ravi Ramesh Pathak; Devapriya Choudhury; Nandula Raghuram (Molecular Genetics and Genomics, 2007)

Bacterial Contamination and Antibiotic Resistance in Fecal Coliforms from Glacial Water Runoff - S. P. Pathak; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

RETRACTED ARTICLE: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2007)

Simulation of Nitrogen Dynamics in Soil Using Infocrop Model - K. N. Ebrayi; H. Pathak; Naveen Kalra; Arti Bhatia; Niveta Jain (Environmental Monitoring and Assessment, 2007)

Isolation and characterization of mutants of Pseudomonas maltophila PM-4 altered in chitinolytic activity and antagonistic activity against root rot pathogens of clusterbean (Cyamopsis tetragonoloba) - E. Yadav; D. V. Pathak; S. K. Sharma; M. Kumar; P. K. Sharma (Indian Journal of Microbiology, 2007)

Long-term yield trend and sustainability of rainfed soybean–wheat system through farmyard manure application in a sandy loam soil of the Indian Himalayas - S. Kundu; Ranjan Bhattacharyya; Ved Prakash; H. S. Gupta; H. Pathak; J. K. Ladha (Biology and Fertility of Soils, 2006)

Osmotic flow through asymmetric membrane: A means for controlled delivery of drugs with varying solubility - Anil K. Philip; Kamla Pathak (AAPS PharmSciTech, 2006)

Dynamics of Organic Carbon and Microbial Biomass in Alluvial Soil With Tillage and Amendments in Rice-wheat Systems - B. Banerjee; P. K. Aggarwal; H. Pathak; A. K. Singh; A. Chaudhary (Environmental Monitoring and Assessment, 2006)

Efficiency of Modified H2S Test for Detection of Faecal Contamination in Water - S. P. Pathak; K. Gopal (Environmental Monitoring and Assessment, 2005)

Use of Flyash and Biogas Slurry for Improving Wheat Yield and Physical Properties of Soil - R. N. Garg; H. Pathak; D. K. Das; R. K. Tomar (Environmental Monitoring and Assessment, 2005)

Soil Properties and Crop Productivity as Influenced by Flyash Incorporation in Soil - Naveen Kalra; M. C. Jain; H. C. Joshi; R. Chaudhary; Sushil Kumar; H. Pathak; S. K. Sharma; Vinod Kumar; Ravindra Kumar; R. C. Harit; S. A. Khan; M. Z. Hussain (Environmental Monitoring and Assessment, 2003)

Toxicity of the Azo Dye Methyl Red to the Organisms in Microcosms, with Special Reference to the Guppy ( Poecilia reticulata Peters) - S. Sharma; S. Sharma; S. Pathak; K. P. Sharma (Bulletin of Environmental Contamination and Toxicology, 2003)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Heavy Metal Accumulation in Lichens from the Hetauda Industrial Area Narayani Zone Makwanpur District, Nepal - Vivek Pandey; D. K. Upreti; Ramayan Pathak; Amit Pal (Environmental Monitoring and Assessment, 2002)

PERMANENT PHENOTYPIC AND GENOTYPIC CHANGES OF PROSTATE CANCER CELLS CULTURED IN A THREE-DIMENSIONAL ROTATING-WALL VESSEL - HONG W. RHEE; HAIYEN E. ZHAU; SEN PATHAK; ASHA S. MULTANI; SARI PENNANEN; TAPIO VISAKORPI; LELAND W. K. CHUNG (In Vitro Cellular & Developmental Biology - Animal, 2001)

Soil Amendment with Distillery Effluent for Wheat and Rice Cultivation - H. Pathak; H. C. Joshi; A. Chaudhary; R. Chaudhary; N. Kalra; M. K. Dwiwedi (Water, Air, & Soil Pollution, 1999)

Activity Accounting Technique for Environmental Noise Assessment in Mechanized Surface Mining - K. Pathak; S. Durucan; S. Kunimatsu (Environmental Monitoring and Assessment, 1999)

Invitro culturedSpodoptera frugiperda insect cells: Model for oxidative stress-induced apoptosis - Seyed E. Hasnain; Tarvinder K. Taneja; Nand K. Sah; Manjari Mohan; Niteen Pathak; Sudhir Sahdev; Mohammad Athar; Satish M. Totey; Rasheedunnisa Begum (Journal of Biosciences, 1999)

Experimental biofilm and its application in malathion degradation - B. Kumari; A. Guha; M. G. Pathak; T. C. Bora; M. K. Roy (Folia Microbiologica, 1998)

HCH and DDT in Surface Extractable Skin Lipid as a Measure of Human Exposure in India - V. K. Dua; C. S. Pant; V. P. Sharma; G. K. Pathak (Bulletin of Environmental Contamination and Toxicology, 1998)

Relationship between sugar maple decline and corresponding chemical changes in the stem tissue - H. K. Mohamed; S. Pathak; D. N. Roy; T. C. Hutchinson; D. L. McLaughlin; J. C. Kinch (Water, Air, & Soil Pollution, 1997)

RELATIONSHIP BETWEEN SUGAR MAPLE DECLINE AND CORRESPONDING CHEMICAL CHANGES IN THE STEM TISSUE - H. K. MOHAMED; S. PATHAK; D. N. ROY; T. C. HUTCHINSON; D. L. MCLAUGHLIN; J. C. KINCH (Water, Air, & Soil Pollution, 1997)

Productivity of annual cropping and agroforestry systems on a shallow Alfisol in semi-arid India - M. R. Rao; C. K. Ong; P. Pathak; M. M. Sharma (Agroforestry Systems, 1991)